Analisis Kelayakan Usaha Wisata Walicung Park Ditinjau dari Aspek Pemasaran dan Lingkungan - Rizki Amalia; Siti Badiatul Umroh; Adji Noerpijar; Rizkia Putri Primadhita; Muhammad Firgi Imansyah; Rama Indra Prasetia; Hagiwara Lakon Pamungkas (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the feasibility of developing Walicung Park Tourism in Brebes Regency based on marketing and environmental aspects. The method used is qualitative descriptive, with data collected through observation, semi-structured interviews with park managers and visitors, as well as relevant documentation. Data analysis was carried out in stages, including data reduction, presentation, and conclusion drawing. The research findings show that from a marketing perspective, Walicung Park has a clear market segmentation, attracts visitors from various regions in Central Java, uses social media strategies for promotion, offers affordable entrance tickets, and has competitive advantages such as natural springs and adequate supporting facilities. From an environmental perspective, the sustainability of this location is supported by the availability of water sources and effective waste management, as well as minimal negative impact on the surrounding community. In addition, this recreational place provides economic benefits by creating jobs and encouraging entrepreneurial opportunities for residents. Based on this, Walicung Park is considered suitable for sustainable development, while continuing to enhance digital marketing efforts, environmental protection, and collaboration with the community.